Functional Genomic Analysis of Fluconazole Susceptibility in the Pathogenic Yeast Candida glabrata: Roles of Calcium Signaling and Mitochondria - Kaur, Rupinder (American Society for Microbiology, 2004)
The pathogenic yeast Candida glabrata exhibits innate resistance to fluconazole, the most commonly used antifungal agent. By screening a library of 9,216 random insertion mutants, we identified a set of 27 genes which upon mutation, confer altered fluconazole susceptibility in C. glabrata. Homologues of three of these genes have been implicated in azole and/or drug resistance in Saccharomyces cerevisiae: two of these belong to the family of ABC transporters (PDR5 and PDR16), and one is involved in retrograde signaling from mitochondria to nucleus (RTG2). The remaining 24 genes are involved in diverse cellular functions, including ribosomal biogenesis and mitochondrial function, activation of RNA polymerase II transcription, nuclear ubiquitin ligase function, cell wall biosynthesis, and calcium homeostasis. We characterized two sets of mutants in more detail. Strains defective in a putative plasma membrane calcium channel (Cch1-Mid1) were modestly more susceptible to fluconazole but showed a significant loss of viability upon prolonged fluconazole exposure, suggesting that calcium signaling is required for survival of azole stress in C. glabrata. These mutants were defective in calcium uptake in response to fluconazole exposure. The combined results suggest that, in the absence of Ca(2+) signaling, fluconazole has a fungicidal rather than a fungistatic effect on C. glabrata. The second set of mutants characterized in detail were defective in mitochondrial assembly and organization, and these exhibited very high levels of fluconazole resistance. Further analysis of these mutants indicated that in C. glabrata a mechanism exists for reversible loss of mitochondrial function that does not involve loss of mitochondrial genome and that C. glabrata can switch between states of mitochondrial competence and incompetence in response to fluconazole exposure.